2011
DOI: 10.1021/ma200572h
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-to-Order Transition of Triblock Comb Copolymer Am+1(BC)m

Abstract: The disorder to order transition of comb copolymer A m+1(BC) m is investigated by the self-consistent field theory. The interaction parameters between the three different blocks are considered by varying the composition of the comb triblock copolymer with the side chain number m = 1 and 3. As the side chain number m increases, the Flory–Huggins interaction parameter of disorder to order transition (DOT) increases and the lowest DOT occurs when the volume fractions of blocks A, B, and C are approximately equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…By comparing these three figures, we also can see that with the increasing of comb side chain number m , the χN of DOT increases largely, which corresponds to the lower temperature to microphase separate, i.e., the system becomes more stable. We can see that the χN of DOT is larger when the coil-comb copolymer has the longer block B or longer block C. This result is different from our previous research on the DOT of A m  + 1 (BC) m [46] because the topological structure between these two kinds of copolymer is different. In this condition, block A is much free and only one end is confined by block B, while blocks B and C are much restricted by the junctions.
Fig.
…”
Section: Resultscontrasting
confidence: 93%
“…By comparing these three figures, we also can see that with the increasing of comb side chain number m , the χN of DOT increases largely, which corresponds to the lower temperature to microphase separate, i.e., the system becomes more stable. We can see that the χN of DOT is larger when the coil-comb copolymer has the longer block B or longer block C. This result is different from our previous research on the DOT of A m  + 1 (BC) m [46] because the topological structure between these two kinds of copolymer is different. In this condition, block A is much free and only one end is confined by block B, while blocks B and C are much restricted by the junctions.
Fig.
…”
Section: Resultscontrasting
confidence: 93%
“…Supposing that the χ value is maintained, a higher χN is required for the microphase separation to occur, because N increases with n. Thus, the (χN) ODT values increase with both n and L C . Results from the SCFT calculations also indicate that the (χN) ODT values increase with architectural periodicity n for the A n+1 (BC) n copolymers [35]. Thus, our results are consistent with the previous theoretical and simulation results.…”
Section: The Critical Values For the Order-disorder Transitionssupporting
confidence: 91%
“…Qian and Wang [35] investigated the (χN) ODT values for the triblock comb copolymer A n+1 (BC) n . According to their results, the (χN) ODT values for copolymers with the side chain number n = 3 was approximately triple the χN for copolymers with n = 1 when the volume fractions of the three or two blocks were equal.…”
Section: The Critical Values For the Order-disorder Transitionsmentioning
confidence: 99%
“…[28][29][30][31][32] Russell and co-workers investigated the unconventional morphologies of symmetric, diblock copolymers as a function of film thickness, 28 and interfacial interactions as early as 1990s. 50,[57][58][59][60][61][62][63][64][65][66] Ross and co-workers successfully explored the graphoepitaxy of spherical morphological block copolymers templated by an array of posts, predicting that the formation of aperiodic templated structures gave an excellent agreement with experimental results. 32 In the following, a series of experimental studies have demonstrated the above results.…”
Section: Introductionmentioning
confidence: 84%
“…56 Especially in recent years, self-consistent field theory (SCFT) has been largely promoted to predict new-fashioned or sophisticated structures versus some phase transitions based on the self-assembly of diblock and triblock copolymers. 50,[57][58][59][60][61][62][63][64][65][66] Ross and co-workers successfully explored the graphoepitaxy of spherical morphological block copolymers templated by an array of posts, predicting that the formation of aperiodic templated structures gave an excellent agreement with experimental results. 50 Meng and Wang carried out a systematic calculation to explore the phase behaviors of symmetric diblock copolymers confined in thin films, observing complex structures of T k (k = 1, 2, 3) combined k layers of regular lamellae with a single layer of perforated lamella for asymmetric surface interactions.…”
Section: Introductionmentioning
confidence: 84%